ANALYSIS OF THE LOYALTY OF CADRES GERINDRA PARTY IN BLITAR - Mujib Mujib; Hery Suprayitno (JOSAR (Journal of Students Academic Research), 2020)
This study is to find out how much cadre loyalty to Gerindra party in Blitar. The object of the research is the Gerindra party cadres. A sample is a set or part of a population unit. The sample selection is done by using purposive sampling which is the direct appointment of respondents according to research needs. So the sample size in this study determined 23 respondents.The results of quantitative descriptive statistical analysis conducted using SPSS 16.00 for windows, the loyalty of cadres Gerinda Party Blitar Regency PT. Griya Asri Mandiri Blitar: 50% have a tendency of good loyalty and 50% have a tendency of unfavorable loyalty, it seen in the results of the frequency of loyalty scores of cadres Gerindra Party in Blitar the highest statement.